VD_FINDINFO HC / 2016 / 4 vom 2. Oktober 2015 - VD Tribunal cantonal (2015)
ASSURANCE, INTERMÉDIAIRE, CONTRAT DE TRAVAIL, AGENT, PROHIBITION DE CONCURRENCE | 321a CO, 114 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)